Neonatal thrombocytopenia in neonates born to the mothers with pregnancy-induced hypertension - Chaurasiya, Omshankar; Chhabra, Kawalpreet (Indian Journal of Child Health, 2019)
Introduction: Neonatal thrombocytopenia is a common clinical problem. Thrombocytopenia presenting in the first 72 h is usually secondary to placental insufficiency and caused by reduced platelet production. Objective: The objective is to evaluate the thrombocytopenia and it is associated neonatal and maternal factors in neonates born to mothers with pregnancy-induced hypertension (PIH). Methods: This study was conducted in a tertiary care hospital over a period of 1 year. Mothers with PIH were included in the study. A detailed history of the mother, physical examination, and platelet count of the newborns was done and data collected. Results: A total 111 neonates born to 106 mothers (5 pair of twin babies) with PIH were included in the study. The male-to-female ratio in these newborns was 1:1.05 with 59.4% being low birth weight (LBW), 63% term babies, and 20.72% small for gestational age babies. 59 (53.15%) neonates had thrombocytopenia and 12 with severe thrombocytopenia. Although a higher percentage of thrombocytopenia was noted with primipara, PIH symptoms at <28 weeks, preeclampsia, and untreated mother, these were not statistically significant. Severe thrombocytopenia was 5 times higher in <2.5 kg neonates as compared to >2.5 kg babies (9.0% vs. 1.8%) and 1.5 times in infants <37 weeks vis-a-vis > 37-week infants (8.3 vs. 4.5%). Thrombocytopenia was significantly associated with LBW (odd ratio [OR] - 1.8056; 95% confidence interval [CI]: 0.8395–3.8834, p=0.0305). Severe thrombocytopenia was significantly associated with LBW (OR - 3.08393; 95% CI: 0.7993–184.442; p=0.0329) and with small for gestational age (OR - 7.2625; 95% CI: 2.0471–25.7651; p=0.0021). Conclusion: Premature and LBW neonates born to mothers with PIH should be regularly scrutinized for thrombocytopenia during the early neonatal period. This would reduce neonatal morbidity and mortality. PIH in mothers should be ruled out as a cause of thrombocytopenia in early neonatal life.